The overeager egg (Boxer Books, 2024)
Beautifully illustrated picture book by an award-winning author-illustrator. A little egg falls out of its nest and goes in search of its mommy. Can it find her? He asks lots of other animals for help—but eventually Daddy finds the egg and takes it back to the nest to hatch into a beautiful swan.